Influence over school discipline policy: Variation across levels of governance, school contexts, and time - Curran, F. Chris (Education Policy Analysis Archives, 2017)
Little research explores the relative influence of various stakeholders on school discipline policy. Using data from the SASS and ordered logistic regression, this study explores such influence while assessing variation across schools types and changes over time. Principals consistently rate themselves and teachers as the most influential stakeholders over setting school discipline policy. The proportion of racial minorities in a school predicts greater influence from higher levels of governance while charter schools report less. Increases in influence of principals and teachers over time are documented. The results may inform both policymakers and practitioners as they work to improve equitable disciplinary outcomes for students.